Surviving stateless refugees: the uncertain future of Rohingya’s children in Malaysia - Azlinariah Abdullah; Azharudin Mohamed Dali; Mohamad Rodzi Abd Razak (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2018)
It is unsurprised that Malaysia drawn the mass migration of Rohingya refugees who are fleeing the sporadic massacres as well as the persecution of the Myanmar government. According to United Nations High Commissioner for Refugees (UNHCR), the flow of these refugees accounts to a total of 154,000 as of end of March 2017. 1 The Rohingya refugees have been in Malaysia since the announcement of the genocide campaign by the Myanmar government against the Muslim Rohingyas a year ago. The need to escape the dire situation in Myanmar, which had been done illegally, these refugees, along with their later generations are identified as illegal migrants. From the legal perspective, the Myanmar children who were born in Malaysia considered no-existence as their births were not documented. The situation, therefore, renders the children to be stateless with an unpromising future. Despite the odds and uncertainty, the communities have crafted themselves for life on the fringe, determined to live their lives as decent human beings and continue to remain Muslims. They have survived without identity cards, jobs or even medical coverage. The purpose of this article is to highlight and analyze the discrimination and inequality faced by the Rohingyas in Malaysia, as well as to propose effective steps to eliminate discrimination and promote equality for the Rohingya refugees. This qualitative article, entails long-recognized human rights problems and aim to shed some light upon less well-known patterns of discriminations against the Rohingyas. For the purpose of this research, the author visited two centers for the Rohingya children; one located in Selayang which is on the outskirt of Kuala Lumpur, and the other in Cheras Baru, Selangor. The latter is chartered by the Myanmar Ethnic Rohingya Human Rights Organization Malaysia (MEHROM) which is operated by the Rohingya community themselves. Interviews were carried out with the principals of the aforementioned centers, as well as officials from the UNHCR and the Rohingya.